PENGARUH HARGA TERHADAP LOYALITAS PELANGGAN PADA KONSUMEN: PENGARUH HARGA TERHADAP LOYALITAS PELANGGAN PADA KONSUMEN - Hariyanto, Muhammad Daffa; Yuliana, Priyanda; Raid Kamali, Shofwan; Sanjaya, Vicky F (Faculty of economcs Universitas Singaperbangsa Karawang, 2023)
In an era of increasing business competition, maintaining a loyal customer base is a significant factor for businesses. Customer loyalty helps companies achieve stable sales and provides long-term benefits such as positive recommendations, increased customer loyalty, and sustainable business growth. Price is one of the important factors that influence the marketing of a product. In this study, we, the authors, used quantitative methods. The focus of our research is on measurable and processable data: numbers. According to Arikunto (Arikunto, 2006), quantitative research is a research approach that uses a lot of numbers, from collecting data to interpreting the obtained data and presenting the results. Based on the hypothesized results, we find that the t-statistic value of the impact of price (X1) on customer loyalty (Y) is 13.699, the p-value is 0.000, and the original sample is 0.766. The obtained findings show that price has a positive and significant impact on customer loyalty at Darussalam Computer Center. The impact of price on customer loyalty of Darussalam Computer Center store in Scarameh, Bandar Lampung is positive and significant as it suggests that a proper pricing policy can increase customer loyalty in the store You can think that it is.